Long non-coding RNA LINC00160 functions as a decoy of microRNA-132 to mediate autophagy and drug resistance in hepatocellular carcinoma via inhibition of PIK3R3. (28th May 2020) - Zhang, Wei; Liu, Yahui; Fu, Yu; Han, Wei; Xu, Hongji; Wen, Lijia; Deng, Yu; Liu, Kai
Abstract: The introduction of long non-coding RNAs (lncRNAs) has revolutionized the treatment of hepatocellular carcinoma (HCC). Thus, in the present study, we aimed to evaluate the effect of a newly found lncRNA, LINC00160, on autophagy and drug resistance of HCC. Interaction among LINC00160, miR-132 and PIK3R3 was verified by dual luciferase reporter gene assay. Loss- and gain-of function experiments were conducted in HCC cells to explore the roles of LINC00160, miR-132 and PIK3R3 in HCC by determining cell viability, autophagy and apoptosis. Finally, tumorigenicity in nude mice was established to confirm the in vitro findings. LINC00160 and PIK3R3 were up-regulated but miR-132 was down-regulated in HCC tissues and cells. LINC00160 may regulate miR-132 and PIK3R3 was the target gene of miR-132. LINC00160 increased the expression of LC3I/LC3II and Atg5 but decreased the p62 expression, while silencing of LINC00160 or over-expression of miR-132 suppressed HCC cell viability, autophagy, drug-resistance and tumorigenicity in nude mice but promoted HCC cell apoptosis by inhibiting the PIK3R3 expression. Taken together, silencing of LINC00160 suppresses autophagy and drug resistance in HCC by regulating miR-132-targeted PIK3R3. Highlights: Role of LINC00160 in drug resistance of HCC cells via PIK3R3 is explored. LINC00160 and PIK3R3 are upregulated but miR-132 is downregulated in HCC cells. LINC00160 regulates PIK3R3 expression by competitively biding to miR-132. Silencing LINC00160 inhibited HCC cell autophagy and drug resistance. LINC00160/miR-132/PIK3R3 axis provides new ideas for drug targets of HCC.